Bilingualism, Demographics, and Cognitive Control: A Within-Group Approach - Xie, Zhilong; Zhou, Shuya (Frontiers in Psychology, 2020)
Previous studies have suggested a bilingual advantage in cognitive control as a result of the bilinguals’ language experience. However, the results are controversial as there are various factors (language proficiency, SES, culture, intelligence, etc.) affecting cognitive control. In the current study, after between-group comparisons, we adopted a within-group approach by multiple regressions to investigate whether the performance by10-to-75-year-old participants (N=91) of tasks measuring inhibition, monitoring, and mental set shifting could be predicted by bilingualism, or demographic factors, or both. The results of multiple stepwise regression analyses showed that L2 proficiency was a significant predictor for conflict monitoring and inhibition, education and age were significant predictors for mental set shifting, and SES was a minor predictor for inhibition. These findings provide evidence that cognitive control is affected by both bilingualism and demographic factors. Future studies are encouraged to further identify the relationship between bilingualism and cognitive control from specific bilingual experience.